Determination of connective heat transfer coefficients in an intermittent kiln. (July 2020) - Guerrero Gómez, G; Vera Duarte, L E; Noriega Sánchez, C J
Abstract: The determination of heat transfer coefficients are parameters of great importance when evaluating thermal losses in a system. Therefore, the present work reports the convective heat transfer coefficients in different positions of a rectangular kiln for the production of artisanal ceramic materials, located in Ocaña, Norte de Santander, Colombia, from which the heat losses present in the were determined. As a result, a virtual instrument was designed for temperature acquisition, using a data acquisition card, as well as a chassis and thermocouples generating a temperature report and their respective temperature profiles. The determination of heat transfer coefficients are parameters of great importance when evaluating thermal losses in a system. The energy supplied by the fuel is 51.21 kJ and the energy loss in the walls and floor of the brick kiln is 17.67 kJ, which represents 34.51% of the energy supplied. The thermal gradient in the kiln is not homogeneous, affecting the quality of the products. This will be avoided by building the walls with refractory materials.